Design and Build an Attendance Recording System Based on Face Recognition and RFID Cards - Atmaja, Daffa Novian; Wijayanti, Rieke Adriati; Kusumawardani, Mila (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2025)
The attendance system at Janimani Cafe was conducted manually. Each employee would clock in on a WhatsApp group, accompanied by a selfie. At specific intervals, the manager would manually record attendance by reviewing the chat history in the WhatsApp group and then compiling the data into a spreadsheet on a computer. Previous research utilized RFID with NodeMCU ESP8266 and ESP32-CAM, but had limitations such as the absence of biometric features, the need for further modifications, and network constraints.Therefore, This research designed an attendance system based on face recognition and RFID technology, supported by ESP32-CAM and a web application for data processing. The system was implemented at Janimani Cafe to address the challenges in employee attendance management. This research discusses the design and implementation of the attendance device, the use of ESP32-CAM and RFID, the development of the web application, and the analysis of employee acceptance and satisfaction levels.The results showed that the device can accurately, quickly, and optimally record attendance under various conditions, from a distance of 60 cm, in low and bright light conditions, and at angles of 0 and 315 degrees. Moreover, it facilitates data processing with a user-friendly interface and is well-received by employees due to increased transparency and reduced fraud.